Community Service in Stunting Prevention Efforts with Spinach Product Innovation: Pengabdian Masyarakat dalam Upaya Pencegahan Stunting dengan Inovasi Produk Bayam - Maulina Alfindy; Septina Nur Aini; Dewi Sinta; Nanik Hariyana (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
Stunting is a chronic condition caused by malnutrition since in the womb. Lojejer Village, located in Wuluhan District, Jember Regency, is one of the areas that still experiences stunting problems. Therefore, KKN Collaboration #3 students made efforts to prevent stunting in Jember Regency through a community service program. The focus of the program is to increase public awareness about nutrition for pregnant women and toddlers, as well as introduce spinach processed products, such as spinach pudding. The outreach activities carried out involved posyandu cadres and PKK mothers in Lojejer Village, which succeeded in increasing understanding of stunting. The socialization and demonstration methods were effective in attracting public interest. The evaluation showed an increase in awareness and active participation, which is expected to improve children's nutrition and health. This program emphasizes the importance of collaboration between the government, health workers, and the community for optimal results.